Modelo logístico aplicado a risco de crédito de uma cooperativa do sistema financeiro - Büttenbender, Elisa Oliveira (Universidade do Vale do Rio dos Sinos, 2013)
This paper has as its theme the measurement of the individual credit risk. It approaches the theories linked to risk, risk measures, the Basel agreement and the financial crisis started in 2007, in the United States. It also seeks to explain the risk models taken as traditional: discriminant analysis and logistic regression. It applies the logistic regression econometric model to assess which variables are more likely to appeal to default. These variables are contained in a sample extracted from a database unit of a cooperative of the national financial system in the experienced areas of healthcare and engineering. This peculiarity leads to the analysis of individuals with similar profiles (education, income, education) that allow the customer insolvency.
Keywords: Forecast; Credit; Risk; Default; Previsão; Crédito; Risco; Inadimplência; ACCNPQ::Ciências Sociais Aplicadas::Economia